Humus M.O. 80 as a seed diluent for direct sowing of lettuce - Mesquita, Cesar de Mello; Pereira, Alberto Leandro; Castro, Luiz Antônio Barreto de (Pesquisa Agropecuaria Brasileira, 2014)
M.O. 80, a by-product of lignite production, was used as a seed diluent with the following concentrations: 90, 80, 70, 60, 50 and 0%. A Planet Jr. seed-drill model 300-A was used to sow the treated lettuce seed. Seed use, and thinning operations were recorded. Treatments involving 90 and 80% of M.O. 80 showed economical use of seed in relation to the control (0% of M.O. 80). It was observed that seed-drill discharge increased proportionally with diluent concentration. Concerning to stand the treatment involving 90% of M.O. 80 presented significant differences in comparison to the other treatments. M .O. 80 at a concentration of 90% differed from the levels with respect to thinning 70, 60 and 50%.